Analisis Strategi Bisnis Usaha Mikro Kecil Dan Menengah Toko Kue: Studi Kasus Pada Usaha Kue Bolu Ina Boy - Lucky Mahesa Yahya; Vinda Putri Yanda; Dinda Indriyani; Abdul Hafid (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The goal of business analysis of sponge cake companies is to comprehend the variables that affect their competitive market performance. Numerous important factors, including the external and internal environments as well as social and cultural factors, must be taken into account in this analysis. Several analysis techniques, including SWOT, STP, and market analysis, can be applied to business analyses of sponge cake companies. Finding an overview of the application of SWOT, STP, and market analysis in the